Wybrane problemy profesjonalizacji organów probacyjnych i klasyfikacji sprawców oddanych pod dozór do grup ryzyka - Stańdo-Kawecka, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
A large prison population and high costs of the prison service contribute to rising interest in problems concerning effective correctional interventions and reduction of reoffending. In recent years, efforts aiming at reducing reoffending have resulted in many countries in significant reforms of national probation systems. Professionalization of probation agencies in order to improve their effectiveness has focused on two processes: risk assessment as well as implementation of interventions targeting dynamic risk factors risk management.In Poland, the requirement to assess the offenders’ risk of reoffending was introduced in 2013 by the order of the Minister of Justice. The purpose of this regulation was to adjust — at least to aminimal extent — Polish probation officers’ activities to model of functioning of probation agencies in the United States, Canada and Western Europe, as well as to recommendations included in the European probation rules. Unlike these countries, the probation service in Poland does not have structured risk assessment tools. The order issued by the Minister of Justice provides for only the classification of supervised offenders into risk groups based on arbitrary, rigid and controversial criteria which has little in common with building the probation service focused on risk management in the meaning of current European standards.
Keywords: reoffending; probation agencies; risk assessment; risk management; risk groups